Cell lineage tracing in the human pancreas - Engqvist, Julia (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2007)
Background and aims: The human pancreas is normally proliferatively quiescent; however loss of cells gives a rapid regenerative response to restore a functionally healthy tissue mass. The mechanism for this is unclear and to date research has failed to identify a definitive pancreatic stem cell. Cell lineage analyses are possible in animals by labelling cells with radioactive tags or genetic markers, but this is not feasible in humans. Current human studies rely on stem cell markers, thus there is a need to develop a better technique to track, isolate and identify cells of related origin. Mitochondrial DNA mutations amass naturally within our cells as we age. Therefore, cells formed by division of a stem cell carrying mutated mitochondrial DNA should, given a qualitative assay, permit the progeny of this cell to be traced.